2009
DOI: 10.1111/j.1365-2125.2009.03535.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of efavirenz on high‐density lipoprotein antioxidant properties in HIV‐infected patients

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• In previous work, we showed a long-term and concentration-dependent beneficial effect of the non-nucleoside reverse transcriptase inhibitor efavirenz (EFV) on high-density lipoproteins (HDL) in human immunodeficiency virus (HIV)-infected patients.• Furthermore, it has been suggested that instead of the current practice of only measuring HDL-chelesterol values, the evaluation of HDL function, namely its antioxidant properties, might be an improved tool for identifying s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…ApoL-1 traffics to the trypanosomal lysosome, where the acidic pH causes a conformational change, leading to activation of anion channel function in the apoL-1 N terminus. Lysosomal swelling kills the trypanosome (Perez-Morga et al 2005). Thus, apoL-1 confers innate immunity against this parasite (Wheeler 2010).…”
Section: Hdl and Parasitic Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…ApoL-1 traffics to the trypanosomal lysosome, where the acidic pH causes a conformational change, leading to activation of anion channel function in the apoL-1 N terminus. Lysosomal swelling kills the trypanosome (Perez-Morga et al 2005). Thus, apoL-1 confers innate immunity against this parasite (Wheeler 2010).…”
Section: Hdl and Parasitic Infectionsmentioning
confidence: 99%
“…Also efavirenz, another NNRTI antiretroviral treatment, was associated with HDL particles with a better antioxidant function, i.e., with a higher PON-1 activity. The PON-1 activity of black patients is higher than that found in whites regardless of treatment suggesting that ethnicity should be taken into consideration when studying drug effects on PON-1 activity (Pereira et al 2009). …”
Section: Hiv Infectionmentioning
confidence: 99%
“…The use of some nucleoside reverse transcriptase inhibitors (NRTI) and PIs is associated with an atherogenic lipoprotein profi le ( 35 ), but NNRTIs, such as efavirenz, promote antiatherogenic changes in HDL particles and function, including normalization of size and lipid composition, enhancement of reverse cholesterol transport, and improvement of antioxidant capacity ( 36 ). A previous study from our group showed that NNRTI treatment was associated with a relative normalization of serum apoA-I and apoA-II, as well as HDL-cholesterol concentrations, in HIV-infected patients ( 37 ), which is consistent with the reported beneficial effects of this compound on HDL composition and function.…”
Section: Multivariate Analysis For Pon3 Concentration In Hiv-infectedmentioning
confidence: 99%
“…Some studies have shown that the activity of PON1 may be affected and/or inactivated by oxidative stress, which could explain its reduced activity during HIV-1 infection [ 7 , 13 ]. In individuals infected with HIV-1 without HAART and/or with acquired immunodeficiency syndrome (AIDS), there is an increase in oxidative stress characterized by increased plasma metabolites of lipid peroxidation and/or a quantitative decrease in antioxidants compared to seronegative controls considered to be in a healthy condition [ 14 , 15 ]. Additionally, it seems that this reduction is associated with a decrease in the number of CD4+ T-cells and indicates that reduced PON1 activity is affected by the immune status of these individuals.…”
Section: Introductionmentioning
confidence: 99%